The Conceptualization of Metaphors in the Lyrics of Back Number’sAlbum Magic (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study entitled "Conceptualization of metaphors in the lyrics of Back Number's song album Magic". analyzes the form and meaning of metaphors that appear in the lyrics of Back Number's song on the Magic Album. The discussion is oriented towards cognitive semantic studies with the aim of describing the types of metaphors. The data source in this study was taken from Back Number's album Magic. The method used in this study is descriptive qualitative with a literature review. The theory used is related to the types of metaphors from Lakoff & Johnson. The results of the data analysis in this study found that the forms of metaphors include conceptual metaphors, structural metaphors, orientational metaphors, ontological metaphors, visual/imagination metaphors. The meaning of metaphors shows themes such as inner conflict, social pressure, sacrifice, love, and life's journey. Then found as many as two conceptual metaphor data, two structural metaphor data, four orientational metaphor data, three ontological metaphor data. Based on the distribution of the data, it can be seen that orientational metaphors and ontological metaphors are the most used.
Keywords: metaphor; metaphorical concepts; back number